Assessing the cost of implementing the 2011 Society of Obstetricians and Gynecologists of Canada and Canadian College of Medical Genetics practice guidelines on the detection of fetal aneuploidies. (7th August 2017) - Lilley, Margaret; Hume, Stacey; Karpoff, Nina; Maire, Georges; Taylor, Sherry; Tomaszewski, Robert; Yoshimoto, Maisa; Christian, Susan
Abstract: Background: The Society of Obstetricians and Gynecologists of Canada and the Canadian College of Medical Genetics published guidelines, in 2011, recommending replacement of karyotype with quantitative fluorescent polymerase chain reaction when prenatal testing is performed because of an increased risk of a common aneuploidy. Study Objective: This study's objective is to perform a cost analysis following the implementation of quantitative fluorescent polymerase chain reaction as a stand‐alone test. Results: A total of 658 samples were received between 1 April 2014 and 31 August 2015: 576 amniocentesis samples and 82 chorionic villi sampling. A chromosome abnormality was identified in 14% (93/658) of the prenatal samples tested. The implementation of the 2011 Society of Obstetricians and Gynecologists of Canada and the Canadian College of Medical Genetics guidelines in Edmonton and Northern Alberta resulted in a cost savings of $46 295.80. The replacement of karyotype with chromosomal microarray for some indications would be associated with additional costs. Conclusion: The implementation of new test methods may provide cost savings or added costs. Cost analysis is important to consider during the implementation of new guidelines or technologies. © 2017 John Wiley & Sons, Ltd. Abstract : What's Already Known About the Topic? Genetic laboratories are faced with financial challenges associated with the implementation of new technologies. Quantitative fluorescent polymerase chain reaction (QF‐PCR) is a well‐accepted method to diagnose common aneuploidies in a prenatal setting. Chromosomal microarray significantly improves the detection rate of chromosome abnormalities compared to karyotype. What does this Study Add? This is the first cost analysis study assessing the implementation of QF‐PCR as a stand‐alone test. The implementation of QF‐PCR as a stand‐alone test provided significant cost saving. Replacement of karyotype with chromosomal microarray will result in additional costs.